The Zionist Paradox : Hebrew Literature and Israeli Identity - Shṿarts, Yigʼal (Book collections on Project MUSE., 2014)
A comprehensive reinterpretation of the development of Hebrew and Israeli literature against the backdrop of the Zionist ideal.